2000
DOI: 10.1163/156856200743823
|View full text |Cite
|
Sign up to set email alerts
|

In vitro testing of ten bone cements after different time intervals from polymerization

Abstract: Biological response of cells to implanted bone cement is a fundamental but often neglected issue in successful cemented implants. In this study, ten acrylic bone cements for orthopedics were assayed using two different in vitro testing methods on L929 cells. The cements were mixed as prescribed, cured for either 1 h or 7 days and then extracted in minimum essential medium (MEM) according to the ISO standard for the preparation of samples. For the evaluation of cytotoxicity, the neutral red uptake assay (NRU) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…These conclusions are consistent with previous results using different cell culture systems: we found that CMW1 acts on apoptosis-driving genes in human lymphocytes, and Cerim LT and CMW2, as well as Zimmer LV and CMW1, have been shown to be cytotoxic to L929 fibroblastic cells after 24 h. 22,5 Oxygen-derived free radicals are involved in apoptosis/necrosis, and a relationship between their concentration and the mode of cell death is likely to exist. We also suggest that the response of cells to toxic agents may depend not only on their concentration, but also on the persistence of the insult over time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These conclusions are consistent with previous results using different cell culture systems: we found that CMW1 acts on apoptosis-driving genes in human lymphocytes, and Cerim LT and CMW2, as well as Zimmer LV and CMW1, have been shown to be cytotoxic to L929 fibroblastic cells after 24 h. 22,5 Oxygen-derived free radicals are involved in apoptosis/necrosis, and a relationship between their concentration and the mode of cell death is likely to exist. We also suggest that the response of cells to toxic agents may depend not only on their concentration, but also on the persistence of the insult over time.…”
Section: Discussionsupporting
confidence: 92%
“…5 In this article, the mechanism of cell death induced in vitro by ten cements currently employed in prosthetic surgery, mainly hip replacements, was studied.…”
Section: Introductionmentioning
confidence: 99%
“…These results confirm the findings of another group, which analyzed cell proliferation of various acrylic bone cements added at different time intervals after polymerization 31,32 . They found that cytotoxic effects of these cements are inversely proportional to their polymerization time, which means that toxicity of PMMA-based cements decreases with proceeding polymerization time.…”
Section: Discussionsupporting
confidence: 89%
“…In other experiments, we found that the undiluted extract of CMW 2 ® was cytotoxic for the mammalian broblasts, while the viability of the cells incubated with CMW 1 ® was 70% of the control [18]. Toxicity was correlated to the content of barium sulphate and benzoyl peroxide, but not to N,N-dimethyl-paratoluidine.…”
Section: Discussionmentioning
confidence: 64%